Analysis and Design of Irrigation Pumps Using Hybrid Solar-Grid Energy with Arduino Uno Control - Mangera, Paulus; Cipto, Cipto (Faculty of Engineering, Universitas Tanjungpura, 2025)
The need for a reliable water supply system and encourages the development of renewable energy technology based on solar power. This study designs and builds a hybrid solar-grid energy system to operate a 12V submersible pump based on an Arduino Uno microcontroller that combines a 200 Wp solar panel energy source and a grid electricity source, with a PWM charge controller and energy storage using a 12V 70Ah lead-acid battery. The 125W submersible pump is the main load for water distribution. Photovoltaic Power Output (PVOUT) map data, Merauke Region has an average annual solar energy potential of 1600